(untitled) (Research, Society and Development, 2025)
Introduction: Pancreatic pseudocyst is a complication related to acute pancreatitis, chronic pancreatitis, and other aggressions to the pancreatic parenchyma, leading to the formation of fibrotic tissue. Methodology: This article aims to review, in the scientific literature of the main databases, information on pancreatic pseudocysts, highlighting the anatomical aspects. Discussion: The pseudocyst is a peripancreatic fluid collection rich in various pancreatic enzymes, with the potential to develop complications such as infection, hemorrhage, gastric obstruction, or biliary obstruction. In 90% of cases, it resolves spontaneously without therapeutic assistance when smaller than 5 cm, but in larger cases, surgical intervention may be necessary. Its formation results from inflammatory events in the pancreatic parenchyma, whether acute or chronic, which facilitate enzyme leakage and the rupture of associated ducts, leading to fibrosis and cystic tissue formation. The main surgical procedures available for treatment include endoscopic drainage, percutaneous drainage, endovascular therapy, and open surgery. Conclusion: Pancreatic pseudocyst has the potential for severity depending on risk factors such as a size greater than 6 cm and the presence of necrosis, which may evolve with complications, requiring surgical approaches that include endoscopic, endovascular, and open surgery alternatives, depending on the comorbidities and clinical indications of each patient.